Retroperitoneal Neuroblastoma in the Adult: about a case - Croci, Fabio; Gastambide, Carmelo; Real, Julio; Aguiar, Alberto (Cirugía del Uruguay, 1983)
The authors present one case of retroperitoneal neuroblastoma ln one adult; a rare condition at thil atage of life. This condition presented disg1.1Ut,d. as an acute obstrucUve colecystopathy. The diagnosis could only be made by the pathologist. The existence of tumor "maturity" Is emphasl.zecL The treatment was complete aurglcal reaecil.OD along with radiotherapy,